M19 A pilot study of endotyping in bronchiectasis. (12th November 2019) - Chew, V; Davidson, R; Davison, J; Davies, G; Jones, G; Jiwa, K; De Soyza, A
Abstract : Aim: Bronchiectasis is increasingly common and has diverse aetiologies. It is commonly viewed as a neutrophilic disease but our prior data has shown some patients are highly eosinophilic. We aimed to extend this by undertaking multikine cytokine analysis. Method: 53 patients of varying bronchiectasis severity were recruited in our regional bronchiectasis service. Multiple cytokines (Vascular Endothelial Growth Factor (VEGF), Tissue Necrosis Alpha(TNF-A), Interleukin 4, 5, 6, 10, 17 were measured with MSD kits. We counted sputum eosinophil and recorded blood eosinophils from routine FBC. We compared our data against the severity based on the bronchiectasis severity index (BSI) which classifies the disease severity into mild, moderate and severe and compared using ANOVA. Results: Of the 53 patients 9 patients had mild BSI severity, 22 were moderate and 22 were severe. Levels of VEGF, TNF-a, Interleukins 4, 5, 6, 10, 17, sputum and blood eosinophils were not correlated with the severity of bronchiectasis, all P values of >0.05. These data extend our observations in 110 patients where TNF and VEGF were not correlated with BSI. IL-8 was statically significant but not a pattern that was expected. This may be due to the sample size. Conclusion: We saw no statistically significant association between the level of cytokines and eosinophils in both blood and sputum with the severity of bronchiectasis. This may reflect the sample size and larger studies should be conducted. There was a large range for each parameter detected however suggested bronchiectasis is highly heterogenous. Future studies targeting distinct pathways may need to consider enriching for certain endotypes.